Development of a novel platform of virus-like particle (VLP)-based vaccine against COVID-19 by exposing epitopes: an immunoinformatics approach. (November 2020) - Ghorbani, A.; Zare, F.; Sazegari, S.; Afsharifar, A.; Eskandari, M.H.; Pormohammad, A.
Abstract: The emergence of a rapidly spreading and highly infectious coronavirus disease 2019 (COVID-19) outbreak by a novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused a global pandemic with unprecedented social and economic dimensions. Therefore, the development of effective strategies is urgent to control the COVID-19 outbreak. According to recent investigations, cell entry of coronaviruses relies on binding of the viral spike glycoprotein to the host cellular receptors. Therefore, the present study aimed to predict immunogenic epitopes in silico by analysing the spike protein. In parallel, by screening the immunogenic SARS-CoV-2 spike-derived epitopes provided in the literature, we chose a set of epitopes that we believed would induce immunogenic response. Next, provided with the epitopes selected by using both approaches, we performed immunoinformatic analysis that mapped identically to the antigen regions and antigenic properties. Finally, after selecting a screened set of epitopes, we designed a novel virus-like particle vaccine optimized to be produced in plants by using molecular farming biotechnology techniques. Our assay may be used as a starting point for guiding experimental efforts towards the development of a vaccine against SARS-CoV-2.